(untitled) (Світ фінансів, 2017)
Смирнова Е. В. Преобразования Налогового кодекса РФ и их влияние на трансфертное ценообразование. Выявлено основные изменения в НК РФ, оценено и спрогнозировано влияние этих изменений на проблемы трансфертного ценообразования в РФ, учитывая мировой опыт в данном вопросе. Smirnova K. Transformations of the Tax code of the Russion Federation and their influence on the transfer pricing. Basic changes in the Tax code of the Russion Federation are exposed, influence of these changes on the problems of the transfer pricing in the Russion Federation are appreciated, taking into account world experience in this question.